Evolving Dimensions of Security and Its Relevance in Nepal - Kharel, Aswasthama Bhakta (Interdisciplinary Journal of Management and Social Sciences, 2021)
“Security” has been defined in different ways by different political scientists, economists, researchers and authors according to the change in course of time and the emergence of the feel of its necessity in various fields. Security includes absence or resilience against potential damage or harm, presence of essential goods, containment and feel of being secured and protected. The evolving dimensions of security concerns about the protection of people not only against war and several forms of unstructured violence but also against hunger, diseases, terrorism, environmental degradation and other global issues. This sketches the globalization of security concept dealing with the state-security and the human security. Numbers of new and challenging security issues are being observed as the world has entered into the economy and power competition among different countries and allies of the countries. This demands for the implication of reformed and effective security strategies. Whereas, Nepal being a South Asian country and a country that is just transitioning from a decade long insurgency and political instabilities, has been facing numerous security matters in national and international levels that are required to be resolved through fruitful initiatives and practical approaches. There is a need of comprehensive and co-ordinate approach to reform the security sectors of Nepal for overall peace and prosperity in the country. The research here is done for the same on the basis of documentary analysis of different journals, public documents, reports, articles, books and research papers from which factual data are included.